Using Keyword – Instruction on Developing Iraqi Intermediate Students’ Vocabulary - Obaid, Sura Abbas; Mohammed Muslim, Abd Ali Nayif Hassan Afrah (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims at using Keyword Based Instruction on Iraqi EFL Second Intermediate Class Students’ Vocabulary Performance. The researcher followed the experimental design into which she has randomly chosen a sample being selected from the 2nd intermediate in Muslim bin Osageh intermediate school for boys. The sample of the present study divided into two groups, experimental and control, each of which includes 47 students. The experimental group was instructed through the keyword method and the control group learned vocabulary through the traditional method. The researcher to be used as pre-test and post-test. A T- test formula for two independent samples is used to analyze the obtained data. The results were found that students in the experimental group significantly outperformed the students in the control group in vocabulary performance by keyword method. Overall, this study illustrated that the use of keyword method can largely reduce learners’ problems in the acquisition and retention of L2 words. The findings of this research may have pedagogical implications for teachers and learners.